Strategic Marketing for Nonprofit Organizations / Fifth Edition - Andreasen R. Alan; Kotler Philip (Prentice Hall, 1996)
Preface, Acknowledgements, Developing a Customer Orientation, Strategic Planning and Organization, Developing and Organizing Resources, Designing the Marketing Mix, Controlling Marketing Strategies, Index.
Preface, Acknowledgements, Developing a Customer Orientation, Strategic Planning and Organization, Developing and Organizing Resources, Designing the Marketing Mix, Controlling Marketing Strategies, Index.